KAJIAN KARAKTERISTIK GERAK ROLL PITCH TRIMARAN DALAM VARIASI LAMBUNG CHINE - Alif Wisnuardi (2022)
Trimaran is a ship that has 3 hulls consisting of a main hull and a side hull. This study aims to vary China by using the main measure. The ship model, namely the AMECRC 9 series model and modified on the Hull with Chine Shape, carried out a Study of Analysis of Roll Pitch dynamics stability with Velocity Variation Fn 0.3; 0,5; 0,7; 0,9; 1,3 from the analysis that was carried out using the chine drajat hull shape experienced a decrease in the degree of movement, especially in the roll dynamics, and when Fn 0.9 to 1.3 the speed affected the dynamic power the higher because of the friction in the water submerged area